Doing Well by Doing Good: The S in Corporate Social Responsibility and Efficiency Performance - Qian, Long Kweh; Wen-Min, Lu; Noor Azlinna, Azizan (2014)
This paper examines the relationship between the social ratings dimensions (the S) in corporate social responsibility (CSR) and corporate performance. Using a twostage approach, we first evaluate the efficiency and metafrontier framework of the U.S. telecommunications industry. In the second stage, we run regression analyses to examine the relationship between the S in CSR and corporate performance. Our first-stage findings show that the sample companies should first improve their scale inefficiencies rather than the inefficiencies in management practices. With regards to the metatechnology ratios, we provide an insight on the potential improvement in performance caused by changes in the production environment. Our second-stage analyses including OLS, two-stage least squares (2SLS), and truncated regression with a bootstrapping approach show that a significantly positive relationship exists between the S in CSR and corporate performance. Taken together, this study would contribute to increased understanding of the contribution of the S in CSR to the performance of the U.S. telecommunications companies.